Evaluation of autoantibodies against oxidized LDL (oLAB) and blood antioxidant status in professional soccer players - Klapcinska, B.; Kempa, K.; Sobczak, A.; Sadowska-Krepa, E.; Jagsz, S.; Szoltysek, I. (International Journal of Sports Medicine, 2005)
Low-density lipoproteins (LDL) are very sensitive to oxidative processes initiated by oxygen free radicals, known to be produced in large quantities during intense physical exercise. Oxidatively modified lipoprotein particles (oxLDL) are strongly atherogenic and immunogenic, as a consequence specific autoantibodies (oLAB) against oxLDL are produced by the immune system. This study was designed to evaluate the oLAB titres in professional soccer players and to find out whether the immune response to oxidative modification of LDL correlates with the antioxidant status of individual players. Eleven players volunteered to participate in an incremental treadmill running exercise to volitional fatigue twice (in October and January) during the competitive season. Venous blood samples were withdrawn before and 3 min after the cessation of the test. Serum levels of oLAB were measured by ELISA (Biomedica). Blood samples were analyzed for glutathione peroxidase, reduced glutathione, superoxide dismutase, catalase and glutathione reductase. The activity of creatine kinase (CK) and concentrations of malondialdehyde (MDA), vitamin E and retinol were determined in plasma. From 11 subjects only in 4 players, in both graded running tests, the oLAB titres were low (< 200 mU · ml-1). The remaining athletes presented elevated oLAB (800 - 1400 mU · ml-1). Significantly lower activities of catalase and glutathione reductase and lower concentration of a-tocopherol were recorded in the 2nd trial. When the data were arranged according to the oLAB titres no significant between-group differences were found in either pre- and post-test activities of antioxidant enzymes or in concentrations of antioxidants. However, significantly higher CK activities and a tendency towards more elevated plasma MDA concentrations were observed in subjects with higher oLAB levels. It seems justified to presume that high titres of antibodies against oxLDL, as evidenced in most of the players, could be accounted for by their higher in vivo susceptibility of LDL to structural modification under conditions of intensive training-induced oxidative stress, despite their apparently normal antioxidant status.